Pathophysiology and clinical manifestations of immune complex vasculitides - Sunderkötter, Cord; Golle, Linda; Pillebout, Evangéline; Michl, Christiane (Frontiers in Medicine, 2023)
Immune complex (IC) vasculitides present inflammations of vessel walls associated with perivascular deposition of immunoglobulins (Igs), mostly ICs. They encompass systemic and skin-limited variants of IgA vasculitis (IgAV), cryoglobulinemic vasculitis (CV), rheumatoid, lupus, and hypocomplementemic vasculitides, serum sickness cutaneous IgM/IgG (non-IgA) vasculitis, and recurrent macular (hypergammaglobulinemic or exertion-induced) vasculitis. Serum sickness and CV fulfill the criteria of a type III hypersensitivity immune reaction as large lattices of the IC precipitate at vessel walls and activate polymorphonuclear neutrophils (PMNs). Immunoglobulin-A vasculitis differs with regard to the causes of perivascular deposition of ICs since here many IgA1 molecules are hypoglycosylated (Gd-IgA1), which appears to facilitate their perivascular deposition in skin and mesangium (via e.g. CD71). The reasons for increased generation of immunoglobulins or formation of IC and their perivascular deposition in either skin or systemic organs are different and not fully explored. A common denominator of OC vasculitides is the activation of PMNs near the vessel wall via Fcy or Fcα receptors. Acute episodes of IgAV additionally require PMNs to become preactivated by IgA1 or by IC already in circulation. This intravascular priming results in increased adherence and subsequently vessel-destructive NETosis when they encounter IgA deposited at the vessel walls. Binding of IgA1 to PMNs in blood stream is associated with increased serum levels of hypogalactosidated IgA1. The characteristic clinical picture of IgAV (and also of so-called IgG/IgM vasculitis) comprises palpable or retiform purpura with a clear predilection for lower legs, probably due to stasis-related reduction in blood velocity, while in other IC vasculitides, additional factors influence the sites of vasculitides. Our knowledge of distinct forms and different pathophysiological pathways of IC vasculitides may lead to in efficacious or targeted therapies. Antibodies to complement components or intestinal budesonide for IgAV are promising agents (the latter suppresses the pathophysiologically related IgA nephropathy by reducing the generation of mucosal IgA.